Breaking the chain : the Guard Dog story - McDonnell, Patrick, 1956- (Abrams ComicArts, 2024)
"For seven weeks in fall 2023, Patrick McDonnell's ... comic strip MUTTS told a long-awaited tale that broke our hearts and gave us hope. Now, collected for the first time and in color, is the complete Guard Dog story, along with real-life stories of rescue and resources for readers who want to take action to help ensure that no dog is tied to a stake and denied their freedom"--Page 4 of dust jacket.